Inclusion initiated fracture in spring steel under axial and torsion very high cycle fatigue loading at different load ratios. (May 2020) - Karr, Ulrike; Sandaiji, Yusuke; Tanegashima, Ryota; Murakami, Shogo; Schönbauer, Bernd; Fitzka, Michael; Mayer, Herwig
Highlights: Tension and torsion cycling and load ratio influence type of crack starting inclusion. Interface fracture at aluminates and particle fracture of MnS inclusions initiates cracks. VHCF strength is determined by a threshold condition for crack propagation. Size effect leads to smaller mean inclusion sizes in torsion compared to tension loading. Ratio of shear and tensile cyclic strength is 0.86 for stresses at same size inclusions. Abstract: Inclusion initiated fracture under axial and torsion very high cycle fatigue loading at load ratios R = −1, 0.1 and 0.35 is compared. High strength spring steel with intentionally increased density of aluminate inclusions was tested at ultrasonic frequency. Failures under axial loading started at internal aluminate inclusions at all load ratios, and at aluminate and MnS inclusions in cyclic torsion at positive load ratios. Considering crack initiation at same size aluminate inclusions, a cyclic torsion stress amplitude at the inclusion that is a factor 0.86 ± 0.05 smaller than the cyclic tension stress amplitude has an equally detrimental effect on cyclic strength.